The Influence of Plan Demographics on Contribution Behavior of 401(k) Participants. Issue 1 (March 2017) - Park, Youngkyun
Abstract: This article examines the influence of plan demographics, which is defined as the salary and tenure composition of a plan, on contribution behavior of 401(k) participants. Results using a large sample of 401(k) plans show that plan demographics influence participant contribution rates directly or through interaction with individual demographic characteristics. A participant's contribution rate can be varied by 1.6–3.0 percentage points for each age between 25 and 64, depending on what plan demographics she is exposed to. In addition, for the decision to contribute the maximum allowed amount, plan demographics significantly interact with individual demographic characteristics.